Home
О нас
Products
Services
Регистрация
Войти
Поиск
SergeySuperr
@SergeySuperr
August 2021
1
10
Report
Решите задачу №1, срочно, 40б, лучше с объяснением
Please enter comments
Please enter your name.
Please enter the correct email address.
Agree to
terms of service
You must agree before submitting.
Send
Answers & Comments
adik61
Y=(k-1)x-2k
M(6;0)
по условию M ∈ y(x)
⇒ 0=(k-1)*6-2k
6k-6-2k=0
4k=6
k=1.5
Ответ: 1.5
2 votes
Thanks 1
SergeySuperr
Спасибо, скоро будут ещё задачи))
×
Report "Решите задачу №1, срочно, 40б, лучше с объяснением..."
Your name
Email
Reason
-Select Reason-
Pornographic
Defamatory
Illegal/Unlawful
Spam
Other Terms Of Service Violation
File a copyright complaint
Description
Helpful Links
О нас
Политика конфиденциальности
Правила и условия
Copyright
Контакты
Helpful Social
Get monthly updates
Submit
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
M(6;0)
по условию M ∈ y(x)
⇒ 0=(k-1)*6-2k
6k-6-2k=0
4k=6
k=1.5
Ответ: 1.5